Strategic Manipulation of Internet Opinion Forums: Implications for Consumers and Firms - Dellarocas, Chrysanthos (Management Science, 2006)
There is growing evidence that consumers are influenced by Internet-based opinion forums before making a variety of purchase decisions. Firms whose products are being discussed in such forums are therefore tempted to manipulate consumer perceptions by posting costly anonymous messages that praise their products. This paper offers a theoretical analysis of the impact of such behavior on firm profits and consumer surplus. There are three main results. First, if every firm’s manipulation strategy is a monotonically increasing (decreasing) function of that firm’s true quality, strategic manipulation of online forums increases (decreases) the information value of a forum to consumers. This result implies the existence of settings where online forum manipulation benefits consumers. Second, equilibria where strategies are monotonically increasing (decreasing) functions of a firm’s true quality exist in settings where the firm’s net payoff function, inclusive of the cost of manipulation, is supermodular (submodular) in the firm’s quality and manipulation action. Third, in a broad class of settings, if the precision of honest consumer opinions that firms manipulate is sufficiently high, firms of all types, as well as society, would be strictly better off if manipulation of online forums was not possible. Nonetheless, firms are locked into a “rat race” and forced to spend resources on such profit-reducing activities; if they don’t, consumer perceptions will be biased against them. The social cost of online manipulation can be reduced by developing “filtering” technologies that make it costlier for firms to manipulate. Interestingly, as the amount of user-contributed online content increases, it is firms, and not consumers, that have most to gain from the development of such technologies.